(untitled) (Swiss Medical Weekly, 2012)
BACKGROUND: Intracoronary injection of autologous bone marrow-derived mononucleated cells (BM-MNC) may improve LV function shortly after acute ST elevation myocardial infarction (STEMI), but little is known about the long-term durability of the treatment effect. METHODS: In a single-centre trial a total of 60 patients with acute anterior STEMI, successful reperfusion therapy and a left ventricular ejection fraction (LVEF) of <50% were screened for the study. 23 patients were actively treated with intracoronary infusion of BM-MNC within a median of 3 days. The open-label control group consisted of 19 patients who did not consent to undergo BM-MNC treatment but agreed to undergo regular clinical and echocardiographic follow-up for up to 5 years after AMI. RESULTS: Whereas at 4 months there was no significant difference between the increase in LVEF in the BM-MNC group and the control group (+7.0%, 95%CI 3.6; 10.4) vs. +3.9%, 95%CI –2.1; 10), the absolute increase at 5 years remained stable in the BM-MNC but not in the control group (+7.95%, 95%CI 3.5; 12.4 vs. –0.5%, 95%CI –5.4; 4.4; p for interaction between groups = 0.035). DISCUSSION: In this single-centre, open-labelled study, intracoronary administration of BM-MNC is feasible and safe in the short term. It is also associated with sustained improvement of left ventricular function in patients with acute myocardial infarction, encouraging phase III studies to examine the potential BM-MNC effect on clinical outcome.